The Effect of Downsizing, Merger & Acquisition, and Transformational Leadership on Company Performance - Wibowo, Heru (Advances in Social Sciences Research Journal, 2020)
Do downsizing and merger & acquisition significantly and positively affect a company performance? Previous studies on the case showed contradictory results. The result of this research supports that downsizing and merger & acquisition do not positively and significantly affect company performance. Standardized regression weights coefficients on AMOS output for both variables of downsizing and merger & acquisition are -0.0787 and -0.0109, each. Thus, downsizing and merger & acquisition actually have negative impacts on company performance. Similar coefficient for the variable of transformational leadership is 0.7611; it has a positive and significant impact on company performance. Research’s respondents are 327 employees of PT Holcim Indonesia Tbk. Test of Cronbach’s Alpha gives 0.886 indicating that the research data is reliable. Some tests of the research model yield good fit for CMIN/df (1.41), RMSEA (0.04), RMR (0.04), AGFI (0.92), and CFI (0.98), as well as acceptable fit for GFI (0.94) and NFI (0.94). Transformational leadership needs to be applied continuously to improve company performance. Transformational leader shall not put downsizing and merger & acquisition from corporate agenda because they both have a negative impact on company performance.